Implementasi metode mozaik untuk mengenalkan huruf vocal pada anak tunagrahita ringan - Milatul Zulfa (Jurnal Pendidikan Edutama, 2020)
Abstract: This research aims to determine the implementation process or the application of the mosaic method in introducing vowels for mildly retarded children who are in grade 1 at Giwangan Elementary School in Yogyakarta. In addition, this research also aims to determine the changes that occur in mildly retarded students after using the mosaic method in learning Indonesian, specifically to introduce vowels. This research uses qualitative methods with descriptive qualitative research. The subjects in this research ware 1st grade of mildly retared student. The object of this research is the application of the mosaic method as a solution to introduce vowels in mildly retarded children. The data collection techniques used observation, interviews, documentation, and field notes. The results of this research indicate that by using the mosaic method in learning the introduction of vowels in mild retarded children is actually feeling very enthusiastic and have a spirit of learning rather than by using methods that have been previously applied. In addition, the subject was very happy and painstaking with little by little sticking pieces of paper that were pasted and arranged to be a letter in question.